Pengaruh Digital Marketing, Kualitas Produk Dan Kualitas Layanan Pada Keputusan Pembelian Ulang Pada Coffee Shop Waktu Kopi PPS - Silfiyyatur Rifqiyyah; Moh. Agung Surianto (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The purpose of this study is to investigate the implications of Digital Marketing, Product Quality, as well as Quality of Service on Re-buy decisions at the Coffee Shop Time Coffee PPS. The study applies a quantitative approach, which refers to a method of study that examines a particular population or sample, aggregates data through a study instrument, analyzes data statistically, with the aim of testing the hypothesis that has been put forward. The sample of this study was 160 people, selected through purposive sampling techniques. The results of the study interpreted Digital Marketing as well as the Quality of Service did not imply significantly on the Re-Buying Decision at the Coffee Shop Time PPS, while the Product Quality influenced the Repurchase Decision in the Coffe Shop time PPS. The authors hoped that the study results would be a guide in designing a more relevant and varied future study.